PENGARUH KARTU KWARTET ANIMALIA DENGAN MODEL TGT TERHADAP PEMAHAMAN MATERI TAKSONOMI HEWAN SISWA SMAN 8 KOTA JAMBI - Retni Sulistyoning Budiarti; Ali Sadikin (BIODIK, 2015)
The card quartet Kingdom Animalia is a card designed with pictures of animals and contain a description of the characteristics of each class that in the Kingdom Animalia. While learning model Team Games Tournament (TGT) is a model student-centered learning, in which students were invited to perform game containing a predetermined competition rules. The purpose of this study was to determine the effect of card usage quartet with learning model (TGT) in the competency test understanding of the material and Animal Taxonomy Percentage student activity during the learning with TGT model took place. The research method using Quasi Experimental Design, where the experimental class and control class is not treated the same as has been formed since the beginning of learning. The results showed that the average value of understanding on animal taxonomy material is higher (6.9) than the control class (4.5). Processing of data by non-parametric statistics (Mann-Whitney U) shows the use of cards that quartet combined with TGT learning model the experimental class provides a very significant influence on the level of 95%. So is the percentage (%) activity in the experimental class (95%) higher than the control class (30%). Based on these results it can be concluded that the use of cards quartet with TGT model material effect on the understanding of the taxonomy of animals and can stimulate the activity of students in the learning process in SMA N 8 Jambi. It is advised to do other similar studies using different learning models. Â  Keywords: card quartet, models Teams Games Tournament (TGT), Animal Taxonomy